Experimental study on the effect of the black wick on tubular solar still performance. (October 2022) - Ahmed, Mohamed M.Z.; Alshammari, Fuhaid; Alqsair, Umar F.; Alhadri, Muapper; Abdullah, A.S.; Elashmawy, Mohamed
Abstract: Solar water desalination is the future alternative to overcome both pollution and water shortage issues. This study describes the effect of a low-cost cotton wick material on the performance of tubular solar still integrated with a parabolic concentrator solar tracking system. Outdoor experimental work was conducted in the real field under July climatic conditions of Ha'il city (995 m above sea level), Saudi Arabia. Results of the tubular solar still with and without the wick were compared to evaluate the achieved improvement of the developed device. Comparative analysis shows a higher performance for the wicked device with a significantly lower freshwater production cost. The use of the black cotton wick increased the device productivity and efficiency by 29.11% and 24.45%, respectively, and lowered water desalination production cost by 40.21%. The device with the wick was able to produce 5.1 L/m 2 day of water desalination with the 40.21% lower cost compared with that of the device without the wick. This productivity can satisfy the basic needs of one person during a day in small and isolated communities.